Standardization of thyroid ultrasound reporting in the community setting decreases biopsy rates. (22nd February 2021) - Ghazizadeh, Shabnam; Kelly, Tracy L.; Khajanchee, Yashodhan S.; Fleser, Jessica; Rozenfeld, Yelena; Neuman, Michael; Hammill, Chet W.; Orr, Lauren; Aliabadi‐Wahle, Shaghayegh
Abstract: Objective: With the rising incidence of thyroid cancer, a standardized approach to the evaluation of thyroid nodules is essential. Despite the presence of multiple national guidelines detailing evaluation and management of these nodules, significant variability exists in the information that is collected and reported to clinicians from diagnostic imaging. The aim of this study was to evaluate the impact of thyroid ultrasound standardization on thyroid cancer detection in a community practice setting. Design: As part of a physician‐driven quality improvement project, a multidisciplinary team created an electronic worksheet to be utilized by sonographers to capture suspicious findings based on societal guidelines and agreed on institutional criteria for recommending fine needle aspiration (FNA) of thyroid nodules. Patients: For a one‐year period prior to and after the intervention, all ultrasounds performed for suspected thyroid pathology, excluding patients undergoing follow‐up imaging, were reviewed at two affiliated community hospitals served by a single radiology and pathology group. Measurements: The number of fine needle biopsies recommended and performed, as well as the percentage of FNAs positive for malignancy were evaluated. Results: A total of 608 and 675 ultrasounds were reviewed in pre‐ and post‐standardization periods, respectively. Following standardization, there was a similar percentage of FNAs recommended (35% vs. 37%, p  = .68), fewer FNAs per total ultrasounds performed (36% vs. 31%, p  = .03), fewer FNAs performed when FNA was not explicitly recommended (9.9% vs. 2.8%, p  = .000046) and an increased detection of cytology consistent with, or suspicious for, malignancy (5% vs. 11.5%, p  = .0028). Conclusions: Standardization of thyroid imaging protocol and management recommendations can reduce the number of FNAs performed and increase the percentage of positive tests in a community setting.